LIBRARY AND INFORMATION SCIENCE EDUCATION IN INDIA: ISSUE AND TRENDS - Singh, S.P. (Malaysian Journal of Library and Information Science, 2003)
This paper traces the emergence of library and information science (LIS) education in India before and after independence. Describes the current status, the different patterns and levels of LIS education, as well as the research programmes being offered by various universities. Provides an overview of the institutions providing LIS courses at various levels through regular courses and open schools. Emphasizes the need for having a national level accreditation body to maintain uniformity and standards in LIS education. Discusses the problems affecting the status of LIS education and suggests ways to solve these problems and the approaches to prepare the LIS professionals to face the growing challenges of the job market.